Identification and Confirmation of Quantitative Trait Loci Associated with Soybean Seed Hardness. Issue 2 (1st March 2015) - Orazaly, Moldir; Chen, Pengyin; Zeng, Ailan; Zhang, Bo
ABSTRACT: Food‐grade soybeans [ Glycine max (L.) Merr.] have specific seed quality requirements, such as seed texture and hardness. Cooked seed hardness is important for soyfood such as natto and edamame, where cooking is required. Texture analysis is time consuming and labor intensive; however, the identification of seed hardness quantitative trait loci (QTL) and associated markers will facilitate the development of elite cultivars through marker‐assisted selection. The objectives of this study were to identify new QTL associated with seed hardness and confirm previously reported QTL. A total of 120 recombinant inbred lines, derived from KS4303sp (soft seeded) × PI 407818 B (hard seeded), were screened with 486 simple sequence repeat markers and tested for cooked seed hardness. The F2:4 and F2:5 lines were grown with two replications at Fayetteville and Keiser, AR, in 2008 and 2009. Interval mapping revealed a new putative QTL for seed hardness ( Ha3 ) in an approximate 46‐cM region and linked to markers Satt547 and Satt414 on chromosome 16. This QTL contributed 32% to seed hardness in the KS4303sp × PI 407818 B population. Single marker analysis revealed 14 markers on seven chromosomes associated with seed hardness. In all environments, Satt254 on chromosome 1, Satt677 on chromosome 7, Satt414, Satt547, and Sat_224 on chromosome 16, and Satt292 on chromosome 20 were significantly associated with seed hardness. A chromosomal region previously reported for hardness (QTL Ha2 ) contained a marker (Satt254 on chromosome 1) that was significant across environments. This study identified a new QTL and confirmed a QTL ( Ha2 ) region that will advance breeding efforts for food‐grade soybean.